Dryland Corn Production in North Central Kansas - Warmann, Gerald W.; Dhuyvetter, Kevin C. (My University, 1995)
This publication provides estimated cost and returns for forward farm planning for dryland corn production in north central Kansas.
MF2161_1995_10
Keywords: MF2161; Crops; Economics; MF